Improving Procedure Text Learning Outcomes Using Cooking Recipes - Nurmariana (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to examine the use of cooking recipes to improve learning outcomes of procedural texts. In learning activities, it was found a problem that student learning outcomes in complex procedure materials were still low. This can be seen from student learning outcomes, where the average value of the learning process is only 45 or 10% above the predetermined KKM, which is 78. Based on this fact, it is necessary to improve the implementation of learning which is carried out in 2 cycles with stages of planning, implementation, observation, and reflection of each cycle. The research method applied was a class action research using Kurt Lewin's model, which was conducted on 33 students of class X IIS 4 consisting of 20 girls and 13 boys at SMA Negeri 1 Tanjungpandan. Based on the analysis of the research data, it can be seen that the use of cooking recipes can improve the learning outcomes of procedural texts in class X semester 1 students of SMA Negeri 1 Tanjungpandan in the 2014/2015 academic year. This is evidenced by the average value obtained by students increasing to 85% with an average value of 90. Keywords: learning outcomes, procedure text, cooking recipes Abstrak Pelitian ini bertujuan untuk mengkaji penggunaan resep masakan dapat meningkatkan hasil belajar teks prrosedur Dalam kegiatan pembelajaran ditemukan masalah bahwa hasil belajar siswa dalam materi prosedur kompleks masih rendah. Hal ini terlihat dari hasil belajar siswa yang rata-rata nilai proses belajar hanya 45 atau 10 % di atas KKM yang telah ditetapkan yaitu 78. Berdasarkan kenyataan tersebut maka perlu dilakukan perbaikan pelaksanaan pembelajaran yang dilakukan dalam 2 siklus dengan tahapan perencanaan, pelaksanaan, observasi, dan refleksi masing-masing siklus. Metode penelitian yang diterapkan adalah penelitian tindakan kelas model Kurt Lewin yang dilakukan pada siswa kelas X IIS 4 berjumlah 33 siswa yang terdiri atas 20 orang perempuan dan 13 orang laki-laki di SMA Negeri 1 Tanjungpandan. Berdasarkan analisis data hasil penelitian, dapat diketahui bahwa penggunaan resep masakan dapat meningkatkan hasil belajar teks prosedur pada siswa kelas X semester 1 SMA Negeri 1 Tanjungpandan tahun pelajaran 2014/2015. Hal ini dibuktikan dengan nilai rata-rata yang diperoleh siswa meningkat menjadi 85 % dengan rata-rata nilai 90. Kata kunci: hasil belajar, teks prosedur, resep masakan